VIOLATION OF POLITENESS MAXIMS IN THE TELEVISION SERIES THE BIG BANG THEORY - Rohmahwati, Agus; Yuliasri, Issy (English Education Journal, 2017)
The aims of this research were to analyze the type of politeness maxims were violated by the speakers, to analyze the purposes of violation, and to evaluate the effects of politeness maxims in the conversation. The data of this research were taken from the television series situation comedy entitled the Big Bang Theory. This research used descriptive qualitative method. It was done by using observation and documentation method. This research found all maxims are violated by the character in the conversation. They are tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, sympathy maxim, consideration maxim, and patience maxim. Furthermore,this research found 12 kinds of purposes of violation made by the speakers. They are warning, advising, admonishing, requesting, suggesting, urging, offering, insisting, alleging, boasting, refusing, and condoling. As the effects of the politeness maxims, the researcher analyzed based on two types the effects of the politeness maxims: violation of politeness maxims and following the politeness maxims. From the analysis, it can be concluded that the use of utterances manner in the conversation is very important to reach the major purpose of politeness principle and the goal of communication can be adhered.